Acute bullous hemorrhagic prurigo: a diagnostic challenge - Haddad, Vidal [UNESP]; Ferreira Fonseca, Cecilia Guimaraes [UNESP]; Mendes, Adriana Lucia [UNESP] (Elsevier B.V., 2020)
Insect bites and bite wounds are quite common and most often have mild repercussions in humans. Statistics on the incidence of accidents caused by insects are not available, and the skin reactions after the bites are not always known. The authors present two cases of patients with hemorrhagic blisters on their hands after tabanidae bites and discuss the factors that cause the problem and the importance of the differential diagnosis of blisters with hemorrhagic content on human skin. (C) 2020 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Anticoagulants; Diptera; Hypersensitivity; Insect bites and stings